(3QSGdI aj Yde GdSdhcs - (3fLe GdOjf CHh GdLfGf CMeO Hf YeQ Hf eMeO GddQGRj GdNjhbj GdcHQj, fLe GOjf GdcHQj,J (B618 (3g` s
(3ChdgG (B:s
(3bGd GdTjN fLe GdOjf GdcHQi GdTQjYI cGdSajfI s
(3BNQgG (B:s
(3Je cdGe GdTjNq s
(3Vef eLehY , JQJjHgG (B: 1s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B218s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3TSJQHJi (B(5067) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs